Electromagnetic wave absorbing metamaterial, preparation method and application thereof

CN123018438APending Publication Date: 2026-10-30XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611293718.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有柔性超材料在实际应用中仍存在明显局限:部分材料虽具备一定柔韧性,但由于吸波剂与柔性基体之间的兼容性不佳,导致有效吸波带宽窄、电磁吸收性能差;而具有宽频吸波性能的材料多基于刚性结构设计,难以满足曲面共形或可穿戴设备对材料柔韧性的要求

Benefits of technology

本发明通过由若干梯台结构单元构成的周期阵列,实现了对电磁波传播路径和损耗机制的精准调控。梯台结构单元的倾斜侧壁,使入射电磁波在单元内部产生多次反射、散射和折射,有效降低了电磁波在材料表面的直接反射(即阻抗匹配效应),使更多电磁波能够进入材料内部,有效提升吸波强度并拓宽有效吸波频带范围。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018438A_ABST
    Figure CN123018438A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of electromagnetic wave absorbing material, and particularly relates to an electromagnetic wave absorbing metamaterial, a preparation method and application, comprising: a plurality of ladder structure units forming a periodic array structure according to a preset arrangement mode; the material of the ladder structure unit comprises: polydimethylsiloxane, a curing agent and a high-entropy oxide composite material; the ladder structure unit comprises a lower surface, an upper surface and an inclined side wall, the area of the lower surface is greater than the area of the upper surface, the lower surface and the upper surface are connected through a plurality of inclined side walls, and the inclined side wall gradually shrinks from bottom to top. The present application realizes multiple scattering and interface polarization of electromagnetic waves by forming a periodic array through the ladder structure unit, significantly improves the absorption efficiency and widens the wave absorption frequency band. The high-entropy oxide composite material provides strong dielectric and magnetic loss; the flexible polydimethylsiloxane matrix ensures that the material still maintains stable structure and wave absorption performance under deformation conditions such as bending and folding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic wave absorbing materials technology, specifically to an electromagnetic wave absorbing metamaterial, its preparation method, and its application. Background Technology

[0002] With the rapid development of flexible electronics, wearable devices, and new military equipment, the electromagnetic environment is becoming increasingly complex, placing higher demands on electromagnetic absorbing materials in terms of performance, deformation adaptability, and stability. An ideal electromagnetic absorbing material not only needs excellent electromagnetic wave absorption capabilities to achieve efficient attenuation of a wide range of electromagnetic waves, but also should possess flexibility and high deformability to adapt to complex working conditions in various scenarios and forms in practical applications. For example, in fields such as flexible displays, wearable sensors, stealth structures for drones, and foldable weapons, materials need to maintain stable mechanical properties and electromagnetic responses under conditions of frequent bending, folding, and even twisting. However, most traditional absorbing materials use magnetic particles, carbon-based materials, or multiphase inorganic composites as their core absorbing components, and their inherent rigid structure and poor interface matching limit their flexible application capabilities.

[0003] Metamaterials, as artificially designed structural functional materials, can achieve special electromagnetic response characteristics through precise design of their unit structures, providing a new path for the design of high-performance microwave absorbing materials. However, existing flexible metamaterials still have significant limitations in practical applications: some materials, although possessing a certain degree of flexibility, suffer from narrow effective absorption bandwidth and poor electromagnetic absorption performance due to poor compatibility between the absorbing agent and the flexible matrix; while materials with broadband microwave absorption performance are mostly based on rigid structural designs, making it difficult to meet the flexibility requirements of curved surfaces or wearable devices. Summary of the Invention

[0004] (a) Purpose of the invention The purpose of this invention is to provide an electromagnetic absorbing metamaterial, its preparation method, and its applications. By constructing a periodic array of stepped structural units, multiple scattering and interface polarization of electromagnetic waves are achieved, significantly improving absorption efficiency and broadening the absorption bandwidth. A high-entropy oxide composite material provides strong dielectric and magnetic losses; flexible polydimethylsiloxane ensures that the material maintains stable structure and absorption performance under bending, folding, and other deformation conditions.

[0005] (II) Technical Solution To address the above problems, this invention provides an electromagnetic absorbing metamaterial, comprising: Several stepped structural units are arranged in a pre-defined pattern to form a periodic array structure. The materials of the tiered structural unit include: polydimethylsiloxane, curing agent, and high-entropy oxide composite material; The tiered structural unit includes a lower surface, an upper surface, and inclined sidewalls. The area of ​​the lower surface is larger than that of the upper surface. The lower surface and the upper surface are connected by a number of inclined sidewalls, which gradually taper from bottom to top.

[0006] In another aspect of the present invention, preferably, the preset arrangement includes the tiered structural units being arranged regularly along the horizontal and vertical directions, and the tiered structural units being aligned in the arrangement direction.

[0007] In another aspect of the present invention, preferably, the high-entropy oxide composite material comprises a carbon-based high-entropy oxide, wherein the carbon-based high-entropy oxide comprises a carbon-based and a transition metal oxide, wherein the carbon-based comprises at least one of mesophase carbon microspheres, carbon black and reduced graphene oxide, and the transition metal comprises at least five of Fe, Co, Ni, Cr, Mn and Cu. The mass ratio of the curing agent to polydimethylsiloxane is 1:(7~10); The high-entropy oxide composite material accounts for 10wt% to 50wt% of the mass of the material in the tiered structure unit.

[0008] In another aspect of the present invention, preferably, the polydimethylsiloxane has a Shore hardness of A20 to A50; The electrical conductivity of the high-entropy oxide composite material is 10~30 S / m.

[0009] In another aspect of the present invention, preferably, the tiered structural unit is a square truss structural unit, and the ratio of the height of the square truss structural unit to the side length of the upper surface to the side length of the lower surface is 4~6:4~8:8~16. The ratio of the side length of the upper surface to the side length of the lower surface is 1:1.5 to 1:4.

[0010] In another aspect, preferably, a method for preparing an electromagnetic absorbing metamaterial is provided, the method being applicable to the electromagnetic absorbing metamaterial described above, the method comprising: The mold for the periodic array structure is prepared according to the preset dimensions; The mold is immersed in a first solution, and after sufficient immersion, it is removed and dried to obtain a treated mold. The first solution includes a release agent and a diluent. The polydimethylsiloxane and curing agent are mixed in a certain mass ratio to obtain a flexible matrix; The high-entropy oxide composite material is added to the flexible matrix according to the mass ratio to obtain a slurry; The slurry is coated onto the surface of the periodic array structure of the treated mold, cured and then demolded to obtain an electromagnetic wave absorbing metamaterial.

[0011] In another aspect of the present invention, preferably, the mold of the periodic array structure is prepared using 3D printing technology, and the material for preparing the mold includes one of photosensitive resin, engineering plastic or nylon material.

[0012] In another aspect of the present invention, preferably, the release agent comprises at least one of fluorinated release agents and silicone release agents, and the diluent comprises at least one of water, ethanol and ethylene glycol; The mass ratio of the curing agent to polydimethylsiloxane is 1:(7~10); The high-entropy oxide composite material has a mass percentage of 10wt%~50wt%; The curing temperature is 15℃~35℃, and the curing time is 48h~72h.

[0013] In another aspect of the present invention, preferably, the step of adding the high-entropy oxide composite material to the flexible matrix according to a certain mass ratio to obtain a slurry includes: The high-entropy oxide composite material is added to the flexible matrix according to the mass ratio and stirred to obtain a pre-mixed slurry. The stirring time is 0.5h to 1h. The prepared slurry is subjected to vacuum degassing treatment to obtain the slurry. The vacuum degassing treatment time is 1h to 2h.

[0014] In another aspect, preferably, the invention relates to the application of an electromagnetic absorbing metamaterial as described above and / or an electromagnetic absorbing metamaterial prepared by the preparation method as described above in the field of electromagnetic absorption in flexible wearable devices, consumer electronics, or military equipment.

[0015] (III) Beneficial Effects The above-described technical solution of the present invention has the following beneficial technical effects: This invention achieves precise control over the propagation path and loss mechanism of electromagnetic waves through a periodic array composed of several trapezoidal structural units. The inclined sidewalls of the trapezoidal structural units cause the incident electromagnetic waves to undergo multiple reflections, scattering, and refractions within the units, effectively reducing the direct reflection of electromagnetic waves on the material surface (i.e., impedance matching effect), allowing more electromagnetic waves to enter the interior of the material, effectively improving the absorption intensity and widening the effective absorption frequency band.

[0016] In terms of material composition, the stepped structure uses flexible polydimethylsiloxane as the matrix and introduces high-entropy oxide composite materials as the microwave absorbing functional component. High-entropy oxides, through multiple loss mechanisms such as lattice distortion, defect polarization, and conductivity loss caused by multi-component solid solution, can achieve broadband and efficient electromagnetic wave attenuation. Flexible polydimethylsiloxane possesses excellent flexibility and tensile strength. The good compatibility between the high-entropy component and the flexible matrix ensures uniform dispersion of the absorbing agent within the structural unit, avoiding the interface debonding or performance degradation problems common in traditional flexible microwave absorbing materials. This allows the metamaterial to maintain a stable geometric configuration and electromagnetic response under complex deformation conditions such as bending, folding, and twisting. It not only achieves broadband and efficient microwave absorption but also significantly improves deformation adaptability, making it suitable for applications such as wearable devices, flexible electronic devices, and stealth applications for curved equipment. Attached Figure Description

[0017] Figure 1 This is a top view of an electromagnetic absorbing metamaterial according to an embodiment of the present invention; Figure 2 This is a schematic diagram of a flexible electromagnetic absorbing metamaterial according to an embodiment of the present invention; Figure 3 This is a schematic diagram of the structural parameters of the periodic unit of the electromagnetic wave absorbing metamaterial obtained in Embodiment 1 of the present invention; Figure 4 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Embodiment 1 of the present invention; Figure 5 This is a schematic diagram of the structural parameters of the periodic unit of the electromagnetic wave absorbing metamaterial obtained in Embodiment 2 of the present invention; Figure 6 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial obtained in Embodiment 2 of the present invention; Figure 7 This is a schematic diagram of the structural parameters of the periodic unit of the electromagnetic wave absorbing metamaterial obtained in Embodiment 3 of the present invention; Figure 8 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial obtained in Embodiment 3 of the present invention; Figure 9 This is a schematic diagram of the structural parameters of the periodic unit of the electromagnetic absorbing metamaterial obtained in Embodiment 4 of the present invention; Figure 10 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 4 of the present invention; Figure 11 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial obtained in Embodiment 5 of the present invention; Figure 12 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial obtained in Embodiment 6 of the present invention; Figure 13 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial obtained in Embodiment 7 of the present invention; Figure 14 This is an electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 8 of the present invention; Figure 15 This is a diagram of the electromagnetic absorption loss of the electromagnetic absorbing metamaterial prepared in Comparative Example 1. Figure 16 This is a diagram of the electromagnetic absorption loss of the electromagnetic absorbing metamaterial prepared in Comparative Example 2. Figure 17 This is a diagram of the electromagnetic absorption loss of the electromagnetic absorbing metamaterial prepared in Comparative Example 3. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments and the accompanying drawings. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.

[0019] Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0020] In the description of this invention, it should be noted that the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0021] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0022] The invention will now be described in more detail with reference to the accompanying drawings. In the various drawings, the same elements are indicated by similar reference numerals. For clarity, the various parts in the drawings are not drawn to scale.

[0023] Example An electromagnetic wave-absorbing metamaterial Figure 1 A top view of an electromagnetic absorbing metamaterial according to an embodiment of the present invention is shown; Figure 2 A schematic diagram of a flexible electromagnetic absorbing metamaterial according to an embodiment of the present invention is shown, as follows. Figure 1 and Figure 2 As shown, it includes: A plurality of tiered structural units are arranged in a pre-defined pattern to form a periodic array structure. This pre-defined pattern defines the spatial layout of the tiered structural units in a planar direction, ensuring that the entire metamaterial exhibits a macroscopically controllable and microscopically continuous periodic structure. The periodic structure of this invention can be achieved through different array arrangements, such as regular matrix arrangements, hexagonal compact arrangements, rhombic array arrangements, or other structural forms that satisfy periodic repetition. By establishing the periodic array, a regular spatial period is formed between the tiered structural units, causing incident electromagnetic waves to undergo multiple scattering, diffraction, and interference within the metamaterial, thereby enhancing the wave absorption effect. In this embodiment, the pre-defined pattern includes the tiered structural units being arranged regularly along the horizontal and vertical directions, with the tiered structural units aligned in the arrangement direction. Specifically, each tiered structural unit is arranged with equal spacing from the center point of its adjacent unit along the horizontal direction, and also with equal spacing from the center point of its adjacent unit along the vertical direction, thus forming a regular two-dimensional grid-like periodic structure. In this arrangement, the tiered structural units are strictly aligned in both the horizontal and vertical directions, making the periodicity of the structure more explicit and enabling it to generate a stable periodic electromagnetic response under the action of incident electromagnetic waves. To avoid the influence of structural gaps on the wave absorption effect, the spacing between the tiered structural units can be designed according to requirements.

[0024] The materials of the stepped structure unit include: polydimethylsiloxane (PDMS), a curing agent, and a high-entropy oxide composite material; PDMS and the curing agent form a flexible, bendable matrix material, and the high-entropy oxide composite material is uniformly dispersed in the matrix to provide absorption mechanisms such as dielectric loss, magnetic loss, or conductivity loss. By adjusting the ratio of the above three components, the material can achieve excellent absorption capabilities in the target frequency band.

[0025] In this embodiment, the high-entropy oxide composite material includes carbon-based high-entropy oxide, which includes carbon-based and transition metal oxides. The carbon-based high-entropy oxide is composed of carbon-based materials and various transition metal oxides. The carbon-based part is used to provide a conductive network and a high specific surface area structure, while the transition metal oxide part is used to introduce multiple types of electromagnetic loss mechanisms, thereby achieving a wide-band absorption enhancement effect. Mesophase carbon microspheres possess a regular spherical structure and excellent electrical conductivity, which can improve the continuity of conductive channels in the composite system. Carbon black has abundant micropores and surface defects, which can provide polarization loss sites. Reduced graphene oxide has a sheet structure and high specific surface area, which can form a two-dimensional conductive network in the composite system, increasing the probability of electronic transitions. The carbon-based components include at least one of mesophase carbon microspheres, carbon black, and reduced graphene oxide. The transition metals include at least five of Fe, Co, Ni, Cr, Mn, and Cu. In the multi-metal system, each metal oxide forms a highly solid-solidified high-entropy structure, causing the material to exhibit complex lattice distortion effects, multiple scattering interfaces, and multiple magnetic coupling behaviors. In this embodiment, the carbon-based high-entropy oxides are FeCoNiCrMnO and reduced graphene oxide (RGO).

[0026] The mass ratio of the curing agent to polydimethylsiloxane is 1:(7~10); this ratio range allows the PDMS matrix to maintain a moderate crosslinking density after final curing, ensuring both its flexibility and bendability, while maintaining sufficient structural strength to support the complete shape of the ladder unit.

[0027] The high-entropy oxide composite material accounts for 10wt% to 50wt% of the total material system by mass. More specifically, it can be 20wt% to 40wt%. When the mass percentage is below 10wt%, the wave-absorbing loss component in the composite system is insufficient, and the wave-absorbing effect is significantly reduced. When the percentage is above 50wt%, the total powder volume is too high, the slurry fluidity is very low, and molding is impossible. Therefore, this range ensures good broadband wave-absorbing performance while maintaining flexibility.

[0028] The Shore hardness of the polydimethylsiloxane is between A20 and A50. This hardness range ensures that the microwave absorbing metamaterial has good flexibility, bendability and deformation recovery ability in practical applications, and can adapt to different usage scenarios such as bending, attaching or rolling, while ensuring that the stepped structure does not suffer significant geometric morphological damage after deformation.

[0029] The high-entropy oxide composite material has an electrical conductivity of 10–30 S / m. This conductivity range is at the level of a typical semiconductor or weak conductor, enabling the formation of a balanced conductivity loss path under the influence of electromagnetic waves: too low a conductivity is insufficient to generate effective current loss, while too high a conductivity may lead to enhanced reflection and hinder absorption. By adjusting the carbon-based structure and the proportion of transition metals, the conductivity can be maintained in the 10–30 S / m range, achieving effective dissipation and absorption of electromagnetic waves.

[0030] The tiered structural unit includes a lower surface, an upper surface, and inclined sidewalls. The area of ​​the lower surface is larger than that of the upper surface. The lower and upper surfaces are connected by several inclined sidewalls, which gradually taper upwards. Through the geometric construction of the inclined sidewalls, the tiered structure achieves a gradually tapering shape from bottom to top. Furthermore, the inclination angle of the inclined sidewalls is 35°-75°, meaning the angle between the inclined sidewalls and the lower surface ranges from 35° to 75°. Within this angle range, a gradient-changing equivalent dielectric parameter can be formed, allowing incident electromagnetic waves to gradually penetrate the material rather than undergoing strong reflection at the material surface, thereby effectively improving absorption efficiency.

[0031] like Figure 2 As shown, (a) illustrates the material mounted on surfaces with different curvatures, and (b) demonstrates the stretching, twisting, and folding effects, ensuring good mechanical properties and flexible deformation capabilities while achieving electromagnetic wave absorption performance. The tilted design controls the width of the gradient transition region, further regulating the propagation path of electromagnetic waves within the structure, resulting in a smoother gradient distribution and reduced interface reflection. Furthermore, the tilt angle can be adjusted according to specific application requirements; for example, it can be appropriately increased when absorbing high-frequency electromagnetic waves to achieve a more pronounced gradient structure effect. Through geometric gradient structures, material composite systems, and a reasonable periodic array arrangement, the electromagnetic wave absorbing metamaterial achieves synergistic optimization of structural flexibility and electromagnetic absorption performance, making it suitable for various applications such as wearable devices, flexible electronics, and stealth materials. The electromagnetic wave absorbing metamaterial obtained in this embodiment satisfies a bandwidth (EAB) of not less than 26 GHz with a -10 dB reflection loss.

[0032] The material system in this embodiment includes flexible polydimethylsiloxane, a curing agent, and a high-entropy oxide composite material. The high-entropy oxide composite material provides multiple absorption mechanisms, including electrical conductance loss, dielectric loss, and magnetic loss, while the flexible matrix ensures the stability of the structure during bending, curling, or deformation. By arranging the stepped structural units in a periodic array, a multi-scale, multi-path electromagnetic wave propagation and scattering network can be formed, thereby achieving broadband absorption and multi-directional incident wave absorption. The periodic array arrangement also enhances the coupling between the stepped units, causing the incident electromagnetic waves to undergo multiple reflections, scattering, and refractions within the units. This effectively reduces the direct reflection of electromagnetic waves at the material surface (i.e., impedance matching effect), allowing more electromagnetic waves to enter the material's interior, effectively increasing the absorption intensity and broadening the effective absorption frequency band.

[0033] The tiered structural unit is a cubic tiered structure unit. The height of the cubic tiered structure unit and the ratio of the side length of its upper surface to the side length of its lower surface are 4~6:4~8:8~16. Both the upper and lower surfaces of the cubic tiered structure unit are square, and the side lengths of its upper and lower surfaces, as well as its structural height, satisfy specific dimensional ratios to ensure the material's wave absorption performance and structural flexibility. Furthermore, the height of the cubic tiered structure unit is 4~6mm, the side length of its upper surface is 4~8mm, and the side length of its lower surface is 8~16mm, with the ratio of the side length of the upper surface to the side length of the lower surface being 1:1.5~1:4. This gives the tiered structure a distinct volumetric gradient characteristic in the vertical direction. This gradient morphology creates a topographic distribution from a "large cross-section" to a "small cross-section" from bottom to top, thereby introducing a continuous gradient of equivalent dielectric constant and magnetic parameters in space. Because the equivalent electromagnetic parameters of high-entropy oxide composites exhibit scale dependence under changes in geometry, this structure can form a layer-by-layer transition from high-reflection regions to low-reflection regions, allowing incident electromagnetic waves to gradually couple into the material interior, reducing interface reflection and improving absorption efficiency. If shrinkage is not significant, the gradient is insufficient, and the impedance matching effect is weakened; if the sidewalls are too steep, a geometric tip effect will occur, causing local scattering enhancement and affecting absorption stability.

[0034] The electromagnetic absorbing metamaterial of this embodiment is formed by uniformly mixing and curing polydimethylsiloxane, a curing agent, and a high-entropy oxide composite material. It achieves a stable periodic array structure without the need for an additional support base, while simultaneously reducing the overall height without sacrificing absorption performance. The baseless structure further enhances the flexibility of the electromagnetic absorbing metamaterial, avoiding the additional spatial and rigid constraints imposed by the base during bending. This allows the material to maintain the integrity of its periodic geometry and absorption characteristics even under bending, torsion, and other deformation conditions, making it more suitable for integrated applications in wearable electronics, curved devices, and complex surface structures.

[0035] Furthermore, this embodiment also provides a method for preparing an electromagnetic absorbing metamaterial, the method being applicable to the electromagnetic absorbing metamaterial described above, the method comprising: A mold for the periodic array structure is prepared according to a preset size. The mold is used to form the periodic tiered structure of the metamaterial, and its manufacturing method is not limited. Common mold-making technologies such as 3D printing, CNC engraving, injection molding, silicone molding, or metal processing can be used. Those skilled in the art can choose one or more combinations of the above methods to prepare the mold based on the product's dimensional accuracy requirements, surface roughness requirements, and production costs. The mold material can be metal, resin, silicone, or other materials with certain mechanical strength and chemical resistance, as long as it can maintain the dimensional stability of the tiered structure. In this embodiment, the mold for the periodic array structure is prepared using 3D printing technology, and the mold material includes one of photosensitive resin, engineering plastics, or nylon. Using 3D printing to prepare molds has advantages such as high molding accuracy, strong structural controllability, and short processing cycle, and is particularly suitable for the mold-making requirements of electromagnetic wave-absorbing metamaterials with micron- to millimeter-level fine tiered structures. The preset dimensions include: the height of the cube structure unit, the ratio of the side length of the upper surface to the side length of the lower surface being 4~6:4~8:8~16; the ratio of the side length of the upper surface to the side length of the lower surface being 1:1.5~1:4. Further, the height of the cube structure unit is 4~6mm, the side length of the upper surface is 4~8mm, and the side length of the lower surface is 8~16mm.

[0036] The mold is immersed in a first solution, and after sufficient immersion, it is removed and dried to obtain a treated mold. The first solution includes a release agent and a diluent. The release agent includes at least one of fluorinated release agents and silicone release agents. The diluent includes at least one of water, ethanol, and ethylene glycol. The fluorinated release agent includes trichloroperfluorooctylsilane and fluorinated polyurethane. The silicone release agent includes emulsion silicone oil and solvent-based silicone oil.

[0037] This embodiment does not limit the specific type of release agent, as long as it can form a stable isolation layer on the mold surface, reduce the adhesion between the flexible substrate and the mold after curing, and meet the demolding requirements. Fluorine-based release agents can form a dense and heat-resistant film on the mold surface, while silicone-based release agents have good lubricity and chemical resistance. The diluent includes at least one of water, ethanol, and ethylene glycol, used to adjust the viscosity and wetting properties of the release agent, making it easier for the release agent to evenly wet the mold surface. Ethanol and ethylene glycol have low surface tension, which can improve the coverage of the solution on complex structural surfaces, thereby improving the demolding effect. The mold is immersed in the above-mentioned first solution to allow the release agent to fully penetrate and adhere to the mold surface. The immersion time can be 20-30 hours, or even 24 hours. After immersion, the mold is removed and air-dried at room temperature or dried at 40℃-60℃ to allow the diluent to evaporate and the release agent to solidify, finally obtaining the treated mold.

[0038] The polydimethylsiloxane and curing agent are mixed at a mass ratio to obtain a flexible matrix; the mass ratio of the curing agent to polydimethylsiloxane is 1:(7~10); those skilled in the art can adjust the specific ratio according to the target flexibility, curing time, and strength requirements. Mechanical stirring, magnetic stirring, or a planetary mixer can be used during mixing to ensure the curing agent is uniformly dispersed in the matrix. To avoid air entrainment, the mixing speed should not be too high; if necessary, slight heating can be applied while stirring to reduce the viscosity of the system and improve uniformity.

[0039] The high-entropy oxide composite material is added to the flexible matrix according to a certain mass ratio to obtain a slurry, comprising: The high-entropy oxide composite material is added to the flexible matrix according to the specified mass ratio and stirred to obtain a pre-mixed slurry. The stirring time is 0.5 h to 1 h. The mass ratio of the high-entropy oxide composite material is 10 wt% to 50 wt%. A lower ratio yields higher flexibility, while a higher ratio provides better microwave absorption performance. This embodiment does not limit the specific composition system, as long as it has good electromagnetic loss capability. To ensure uniform distribution of the high-entropy oxide particles in the matrix, high-speed stirring or planetary stirring can be used for mixing. The stirring time is 0.5 h to 1 h to ensure that the particles are fully dispersed and do not agglomerate.

[0040] The prepared slurry is subjected to vacuum degassing treatment to obtain a slurry. The vacuum degassing treatment time is 1 to 2 hours. After stirring, the prepared slurry is placed in a vacuum environment for degassing treatment to remove air bubbles introduced during stirring. The vacuum degassing time is 1 to 2 hours, and the vacuum degree can be adjusted in stages during the degassing process to avoid slurry splashing. After degassing, there are basically no visible air bubbles inside the slurry, which is beneficial to the integrity of the final molded structure and improves the quality and electromagnetic properties of the molded surface.

[0041] Furthermore, this embodiment also provides an application of the electromagnetic absorbing metamaterial described above and / or the electromagnetic absorbing metamaterial prepared by the preparation method described above in the field of electromagnetic absorption in flexible wearable devices, consumer electronics, or military equipment.

[0042] With the development of flexible electronics, smart textiles, and wearable sensors, wearable devices are increasingly used in daily life and medical monitoring. However, wearable devices are often in close contact with the human body, and the electromagnetic radiation generated by their internal electronic components may affect safety or cause interference between devices. The electromagnetic absorbing metamaterial described in this embodiment has good flexibility, can bend dynamically with the human body, and maintain stable performance. Today's consumer electronic devices have high integration and wide operating frequency bands, making electromagnetic compatibility issues increasingly prominent, especially in miniaturized products. The electromagnetic absorbing metamaterial described in this invention combines lightweight, flexibility, and high loss characteristics, and can be applied to various consumer electronic products through attachment, embedding, or encapsulation. Military equipment has even stricter requirements for electromagnetic shielding, stealth, and anti-interference performance. The electromagnetic absorbing metamaterial provided by this invention has a customizable periodic structure and broadband absorption performance, and can be applied to radar stealth, equipment anti-interference, communication protection, and other aspects. The products prepared by the electromagnetic absorbing metamaterial and its preparation method provided by this invention can be used to achieve lightweight and flexible wave-absorbing protection in the field of flexible wearables, improve electromagnetic compatibility in consumer electronics, and serve as key materials for stealth and anti-interference in military equipment. They have broad application prospects and significant technical value.

[0043] Example 1 A mold with a periodic array structure was fabricated using 3D printing technology, with nylon as the printing material. The height of the tiered structural unit was 5 mm, the side length of the upper surface was 6 mm, and the side length of the lower surface was 12 mm. The printed mold was immersed in an aqueous solution containing trichloroperfluorooctylsilane for 24 hours, followed by drying to form a thin film on its surface, thus obtaining the treated mold. A curing agent and polydimethylsiloxane (PDMS) were mixed at a mass ratio of 1:10. The Shore hardness of PDMS was A35. A carbon-based FeCoNiCrMnO high-entropy oxide material was added. The electrical conductivity of the high-entropy oxide composite material was 20 S / m, and its mass percentage was 30 wt% (the mass percentage of the high-entropy oxide microwave absorber in the slurry). After mechanical stirring for 45 minutes, vacuum degassing was performed. The pressure difference under vacuum conditions caused the residual air inside the polymer to escape. After degassing for 2 hours, a uniform polymer liquid slurry was obtained. The uniform slurry after vacuum degassing is coated into the mold after the pretreatment steps. In a ventilated environment, the curing temperature is 25℃, and after solidification for 60 hours, the mold is demolded to obtain the electromagnetic wave absorbing metamaterial. Figure 1 The finished product of Example 1 is shown. Figure 2(a) shows Example 1 mounted on a base surface with different curvatures. Figure 2 (b) shows the stretching, twisting and folding of Example 1, demonstrating that Example 1 has excellent flexibility, can fit completely to the base surface with different curvatures, and its folding angle reaches 270°, which can meet the requirements of material flexibility for curved surfaces or wearable devices. Figure 3 A schematic diagram of the periodic unit structure parameters of the electromagnetic absorbing metamaterial prepared in Example 1 is shown. Figure 4 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 1 is shown, with an effective absorption bandwidth of 35.90 GHz.

[0044] Example 2 The height of the tiered structure unit is 4mm, the side length of the upper surface is 6mm, the side length of the lower surface is 12mm, and the other parameters are the same as in Example 1. Figure 5 A schematic diagram of the periodic unit structure parameters of the electromagnetic absorbing metamaterial obtained in Example 2 is shown. Figure 6 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 2 is shown, with an effective absorption bandwidth of 28.44 GHz.

[0045] Example 3 The height of the tiered structure unit is 5mm, the side length of the upper surface is 4mm, the side length of the lower surface is 12mm, and the other parameters are the same as in Example 1. Figure 7 A schematic diagram of the periodic unit structure parameters of the electromagnetic absorbing metamaterial obtained in Example 3 is shown. Figure 8 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 3 is shown, with an effective absorption bandwidth of 30.52 GHz.

[0046] Example 4 The height of the tiered structure unit is 5mm, the side length of the upper surface is 6mm, the side length of the lower surface is 15mm, and the other parameters are the same as in Example 1. Figure 9 A schematic diagram of the periodic unit structure parameters of the electromagnetic absorbing metamaterial obtained in Example 4 is shown. Figure 10 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 4 is shown, with an effective absorption bandwidth of 32.34 GHz.

[0047] Example 5 The high-entropy oxide composite material has a mass ratio of 20 wt%, and the other parameters are the same as in Example 1. Figure 11 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 5 is shown, with an effective absorption bandwidth of 26.26 GHz.

[0048] Example 6 The high-entropy oxide composite material had a mass ratio of 40 wt%, and the other parameters were the same as in Example 1. Figure 12The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 6 is shown, with an effective absorption bandwidth of 31.36 GHz.

[0049] Example 7 The high-entropy oxide was FeCoNiCuMnO, and the other parameters were the same as in Example 1. Figure 13 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 7 is shown, with an effective absorption bandwidth of 30.96 GHz.

[0050] Example 8 The high-entropy oxide was CoNiCrCuMnO, and the other parameters were the same as in Example 1. Figure 14 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Example 8 is shown, with an effective absorption bandwidth of 33.30 GHz.

[0051] Example 9 A mold with a periodic array structure was fabricated using 3D printing technology, with photosensitive resin as the printing material. The height of the tiered structural unit was 6 mm, the upper surface side length was 8 mm, and the lower surface side length was 16 mm. The printed mold was immersed in an ethanol solution containing fluorinated polyurethane and dried for 24 hours to form a thin film on its surface, thus obtaining the treated mold. A curing agent and polydimethylsiloxane (PDMS) were mixed at a mass ratio of 1:7. The Shore hardness of PDMS was A20. A carbon-based FeCoNiCrMnO high-entropy oxide material was added. The electrical conductivity of the high-entropy oxide composite material was 10 S / m, and its mass percentage was 10 wt% (the mass percentage of the high-entropy oxide microwave absorber in the slurry). After mechanical stirring for 30 minutes, vacuum degassing was performed. The pressure difference under vacuum caused the residual air inside the polymer to escape. After degassing for 1 hour, a uniform polymer liquid slurry was obtained. The uniform slurry after vacuum degassing is coated into a mold that has undergone the pretreatment steps. In a ventilated environment, the curing temperature is 15℃, and after solidification for 72 hours, the mold is demolded to obtain the electromagnetic wave absorbing metamaterial.

[0052] Example 10 A mold with a periodic array structure was fabricated using 3D printing technology, with engineering plastics as the printing material. The height of the tiered structural unit was 4 mm, the side length of the upper surface was 4 mm, and the side length of the lower surface was 8 mm. The printed mold was immersed in an ethylene glycol solution containing emulsion-type silicone oil for 24 hours, followed by drying to form a thin film on its surface, thus obtaining the treated mold. A curing agent and polydimethylsiloxane (PDMS) were mixed at a mass ratio of 1:8. The Shore hardness of PDMS was A50. A carbon-based FeCoNiCrMnO high-entropy oxide material was added. The electrical conductivity of the high-entropy oxide composite material was 30 S / m, and its mass percentage was 50 wt% (the mass percentage of the high-entropy oxide microwave absorber in the slurry). After mechanical stirring for 1 hour, vacuum degassing was performed. The pressure difference under vacuum caused the residual air inside the polymer to escape. After degassing for 1.5 hours, a uniform polymer liquid slurry was obtained. The uniform slurry after vacuum degassing is coated into a mold that has undergone the pretreatment steps. In a ventilated environment, the curing temperature is 35℃, and after solidification for 48 hours, the mold is demolded to obtain the electromagnetic wave absorbing metamaterial.

[0053] Comparative Example 1 The height of the platform is 2mm, the side length of the upper surface is 6mm, the side length of the lower surface is 12mm, and the other parameters are the same as in Example 1. Figure 15 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Comparative Example 1 is shown, with an effective absorption bandwidth of 17.77 GHz.

[0054] Comparative Example 2 The platform height is 5mm, the upper surface side length is 3mm, the lower surface side length is 12mm, and the remaining parameters are the same as in Example 1. Figure 16 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Comparative Example 2 is shown, with an effective absorption bandwidth of 23.90 GHz.

[0055] Comparative Example 3 The high-entropy oxide composite material accounted for 3 wt% of the total mass, and the remaining parameters were the same as in Example 1. Figure 17 The electromagnetic absorption loss diagram of the electromagnetic absorbing metamaterial prepared in Comparative Example 3 is shown, with an effective absorption bandwidth of 1.97 GHz.

[0056] The samples from Examples 1-10 and Comparative Examples 1-3 were tested. The test method included testing the electromagnetic absorption performance of the electromagnetic absorbing metamaterial as follows: The far-field reflectivity (2-40 GHz) of the absorber metamaterial was measured in a microwave anechoic chamber. Two pairs of double-ridged antennas were used, responsible for the 2-18 GHz and 18-40 GHz frequency bands, respectively. For the target frequency band, one antenna acted as the transmitter and the other as the receiver. The antennas were connected to the VNA via coaxial cables with a cutoff frequency greater than 40 GHz. Before testing, a flat copper plate with the same lateral dimension and thickness as the sample was used to calibrate each measurement. Table 1 shows the test results for Examples 1-10 and Comparative Examples 1-6. Table 1 Test results of Examples 1-10 and Comparative Examples 1-6 In summary, the effective absorption bandwidth and flexibility of the sample in this embodiment are superior to those of the comparative example.

[0057] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the appended claims, or equivalent forms of such scope and boundaries.

[0058] The present invention has been described above with reference to embodiments thereof. However, these embodiments are merely illustrative and not intended to limit the scope of the invention. The scope of the invention is defined by the appended claims and their equivalents. Various substitutions and modifications can be made by those skilled in the art without departing from the scope of the invention, and all such substitutions and modifications should fall within the scope of the invention.

[0059] Although embodiments of the present invention have been described in detail, it should be understood that various changes, substitutions, and modifications can be made to the embodiments of the present invention without departing from the spirit and scope of the invention.

[0060] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. An electromagnetic wave-absorbing metamaterial, characterized in that, include: Several stepped structural units are arranged in a pre-defined pattern to form a periodic array structure. The materials of the tiered structural unit include: polydimethylsiloxane, curing agent, and high-entropy oxide composite material; The tiered structural unit includes a lower surface, an upper surface, and inclined sidewalls. The area of ​​the lower surface is larger than that of the upper surface. The lower surface and the upper surface are connected by a number of inclined sidewalls, which gradually taper from bottom to top.

2. The electromagnetic absorbing metamaterial according to claim 1, characterized in that, The preset arrangement includes the ladder structure units being arranged regularly in the horizontal and vertical directions, and the ladder structure units being aligned in the arrangement direction.

3. The electromagnetic absorbing metamaterial according to claim 1, characterized in that, The high-entropy oxide composite material includes carbon-based high-entropy oxides, which include carbon-based and transition metal oxides. The carbon-based oxides include at least one of mesophase carbon microspheres, carbon black, and reduced graphene oxide. The transition metals include at least five of Fe, Co, Ni, Cr, Mn, and Cu. The mass ratio of the curing agent to polydimethylsiloxane is 1:(7~10); The high-entropy oxide composite material accounts for 10wt% to 50wt% of the mass of the material in the tiered structure unit.

4. The electromagnetic absorbing metamaterial according to claim 1, characterized in that, The Shore hardness of the polydimethylsiloxane is A20~A50; The electrical conductivity of the high-entropy oxide composite material is 10~30 S / m.

5. The electromagnetic absorbing metamaterial according to claim 1, characterized in that, The tiered structure unit is a square tier structure unit, and the ratio of the height of the square tier structure unit to the side length of the upper surface to the side length of the lower surface is 4~6:4~8:8~16. The ratio of the side length of the upper surface to the side length of the lower surface is 1:1.5 to 1:

4.

6. A method for preparing an electromagnetic absorbing metamaterial, characterized in that, The preparation method is applicable to the electromagnetic absorbing metamaterial as described in any one of claims 1-5, and the preparation method includes: The mold for the periodic array structure is prepared according to the preset dimensions; The mold is immersed in a first solution, and after sufficient immersion, it is removed and dried to obtain a treated mold. The first solution includes a release agent and a diluent. The polydimethylsiloxane and curing agent are mixed in a certain mass ratio to obtain a flexible matrix; The high-entropy oxide composite material is added to the flexible matrix according to the mass ratio to obtain a slurry; The slurry is coated onto the surface of the periodic array structure of the treated mold, cured and then demolded to obtain an electromagnetic wave absorbing metamaterial.

7. The preparation method according to claim 6, characterized in that, The mold for the periodic array structure is prepared using 3D printing technology, and the mold is made of one of the following materials: photosensitive resin, engineering plastic, or nylon.

8. The preparation method according to claim 6, characterized in that, The release agent includes at least one of fluorinated release agents and silicone release agents, and the diluent includes at least one of water, ethanol, and ethylene glycol. The mass ratio of the curing agent to polydimethylsiloxane is 1:(7~10); The high-entropy oxide composite material has a mass percentage of 10wt%~50wt%; The curing temperature is 15℃~35℃, and the curing time is 48h~72h.

9. The preparation method according to claim 6, characterized in that, The step of adding the high-entropy oxide composite material to the flexible matrix according to a certain mass ratio to obtain a slurry includes: The high-entropy oxide composite material is added to the flexible matrix according to the mass ratio and stirred to obtain a pre-mixed slurry. The stirring time is 0.5h to 1h. The prepared slurry is subjected to vacuum degassing treatment to obtain the slurry. The vacuum degassing treatment time is 1h to 2h.

10. The application of an electromagnetic absorbing metamaterial as described in any one of claims 1-5 and / or an electromagnetic absorbing metamaterial prepared by the preparation method described in any one of claims 6-9 in the field of electromagnetic absorption in flexible wearable devices, consumer electronics, or military equipment.